Amyloid and APOE4 status interact with age on different medial temporal lobe subregions in cognitively unimpaired elderly. (31st December 2021) - de Flores, Robin; Demeilliez‐Servouin, Solène; Kuhn, Elizabeth; Chauveau, Lea; Landeau, Brigitte; Delcroix, Nicolas; Gonneaud, Julie; Chetelat, Gaël
Abstract: Background: Medial temporal lobe (MTL) subregions, more specifically the CA1 subfield of the hippocampus and the entorhinal cortex (ERC), are particularly affected in Alzheimer's disease (AD). However, the specific impact of amyloid (Aβ) pathology and APOE ε4 on MTL subregional atrophy remains relatively unknown. Our aim was to uncover these effects to further our understanding of the mechanisms underlying MTL atrophy in the context of AD. Method: We used baseline data from 132 unimpaired older adults (mean age: 68.9 ± 3.8 years) from the Age‐Well randomized controlled trial for whom high‐resolution structural MRI (T2‐weighted; 0.4x0.4x2.5mm 3 ), amyloid‐PET (Florbetapir) and APOE genotype were available. Participants were dichotomized into amyloid positive (Aβ+, n=27) and negative (Aβ‐, n=105), and APOE ε4 carrier (ε4+, n=36) and non‐carriers (ε4‐, n=96). Hippocampal subfield (CA1, CA2, CA3, dentate gyrus, subiculum) and extra‐hippocampal region (entorhinal cortex [ERC], Brodmann area [BA] 35 and 36, and parahippocampal cortex [PHC]) volumes were estimated using ASHS and normalized by total intracranial volume. For each subregion, group comparisons were performed (Aβ+ vs Aβ‐ and ε4+ vs ε4‐) using ANCOVAs, including age, sex and education as covariates. Interactions with age ( i.e., Aβ status * age and APOE ε4 status * age) were also investigated for each subregion. Result: No significant differences were observed between Aβ+ and Aβ‐, nor between ε4+ and ε4‐. However, significant Aβ status * age interactions were observed for CA1 and PHC (p<0.05), where volumes were negatively associated with age in the Aβ+ group only (figure 1). In addition, a significant APOE ε4 status * age interaction was found for ERC (p<0.05), where volume was negatively associated with age in the ε4+ group only (figure 2). Conclusion: Overall, our analyses showed that Aβ and APOE ε4 status differentially interact with age on MTL subregions (CA1/PHC and ERC, respectively) in cognitively unimpaired elderly. These observations suggest that the atrophy of MTL regions that are specifically altered in AD relies on distinct mechanisms involving amyloid pathology and APOE ε4. These results are particularly important to develop MRI‐based biomarkers to detect early AD and further our understanding of MTL atrophy in normal and pathological ageing.